(untitled) (LEGAL DIALOGICA, 2025)
This research aims to find out and analyze the validity of the Roya concession deed as a substitute for a mortgage right certificate and to know and understand the procedures and requirements for making a Roya concession deed as a substitute for a mortgage right certificate. The research method used is normative legal research. Based on these problems, there are research results obtained by the author: The basis for making a Roya Konsen Deed as a replacement for a lost Mortgage Rights Certificate, is based on the provisions of the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning Land Service Standards and Regulations Appendix II and the validity of the Roya Konsen deed as a substitute for a mortgage certificate refers to the process of making it which meets the formal and material requirements so that it is not legally defective and has legal force. Making a Roya Consent Deed refers to the conditions that must be fulfilled, including a letter of loss from the police, identity of the parties, settlement letter, Roya cover letter and relevant documents and appropriate procedures so that the Roya Consent Deed can be said to be valid and can be attached as requirements for carrying out the write-off administration process. Research recommendations related to the Roya Consent Deed require the creation of special regulations that regulate in detail the Roya Consent Deed which includes clear and consistent procedures, conditions, mechanisms in all jurisdictions so that interested parties can obtain clear and accurate information. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis keabsahan akta konsen roya sebagai pengganti sertifikat hak tanggungan dan untuk mengetahui dan memahami prosedur dan syarat pembuatan akta konsen roya sebagai pengganti sertifikat hak tanggungan. Metode penelitian yang digunakan adalah penelitian hukum normatif. Berdasarkan permasalahan tersebut terdapat hasil penelitian yang diperoleh penulis: Dasar pembuatan Akta Konsen Roya sebagai pengganti Sertifikat Hak Tanggungan yang hilang, berdasar pada ketentuan Peraturan Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 1 Tahun 2010 tentang Standar Pelayanan dan Pengaturan Pertanahan Lampiran II dan keabsahan akta konsen roya sebagai pengganti sertifikat hak tanggungan merujuk pada proses pembuatannya yang memenuhi syarat-syarat formil dan materil agar tidak cacat hukum dan memiliki kekuatan hukum. Pembuatan Akta Konsen Roya merujuk pada syarat-syarat yang harus dipenuhi, diantaranya Surat kehilangan dari kepolisian, Identitas para pihak, Surat lunas, Surat pengantar roya dan dokumen-dokumen yang relevan hingga prosedur yang sesuai agar Akta Konsen Roya dapat dikatakan sah dan dapat dilampirkan sebagai syarat dalam melakukan proses administrasi pencoretan. Rekomendasi penelitian terkait Akta Konsen Roya perlu dibuatnya regulasi khusus yang mengatur secara rinci tentang Akta Konsen Roya yang mencakup prosedur, syarat, mekanisme yang jelas dan konsisten di seluruh wilayah hukum sehingga pihak yang berkepentingan dapat memperoleh informasi yang jelas dan akurat.